Educational evaluations of children with special needs : clinical and forensic considerations - Breiger, David (Forensic practice in psychology series., 2014)
"This book describes a structured and standardized approach to conducting evaluations of children, specifically to aid in the determination of eligibility for special education services or accommodations in the public school setting. Special attention is paid to independent educational evaluations and situations that may involve considerable tension between families and schools. Both the scholarly literature and the laws that address how a standardized evaluation approach can be conducted are addressed. The chapters provide practical information as well as relevant background material necessary to understand the special education assessment context; this information will assist both psychologists new to and experienced with this area of practice. As a reference, the book facilitates the development of a protocol that guides the evaluation process and minimizes problems with parents or school personnel. As an instructional text, it offers to graduate students and novice psychologists the tools needed to complete educational evaluations"--Book. (PsycINFO Database Record (c) 2013 APA, all rights reserved)